The Use of Student Worksheets on Arabic Learning Outcomes / Istikhdām Waraqah al-Tadrībāt ‘Alā Natījah Ta’allum al-Lughah al-Arabiyyah - Hikmah Nur Fitriani (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2021)
This research aims to know the effectiveness of using the worksheet student on learning Arabic and revealing the motivating and obstacle factors for eighth-grade students at Darul Ulum Islamic Junior High School Ngaliyan Semarang. The type of this research is descriptive qualitative research. The researcher calculated using simple symbols to know the worksheet student's effectiveness by the student's results in the final exam. As a result of this research, the percentage of the successful student in the 8th grade